Ru-ni / nio-mmo catalyst and preparation and application thereof
Patent Information
- Application Number
- CN202510415157.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
该技术采用的催化剂虽然在应用氢解反应过程中可获得较高的产物选择性,但其催化剂载体采用化学沉淀法制备,载体材料的无序组装使得制备出的催化剂在后续活性金属元素负载受到限制,且在催化反应过程,该催化剂仅能使催化剂外表面活性位点发挥催化作用,这进一步限制了该催化剂的催化效率
[0048] Preferably, the mass ratio of lignin to Ru-Ni/NiO-MMO catalyst is 1:(0.5-2).
Smart Images

Figure CN122912873A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomass conversion technology, specifically to a Ru-Ni / NiO-MMO catalyst and its preparation and application, specifically for catalyzing the hydrogenolysis of lignin. Background Technology
[0002] Lignin, the second largest biomass resource in nature, is a three-dimensional network biopolymer composed of three phenylpropane structural units linked by ether and carbon-carbon bonds. It exhibits strong structural stability, weak chemical reactivity, and is difficult to convert and utilize. Only a small amount of lignin is used for high-quality, high-value production, with the majority being directly incinerated or indiscriminately stockpiled, leading to environmental pollution and resource waste. During the catalytic hydrogenolysis of lignin, the benzene ring structure in lignin is less damaged, yielding a liquid-phase product with low viscosity, low oxygen content, and high stability. This method is an effective way to achieve high-quality, high-value utilization of lignin.
[0003] Ni is a commonly used active component in hydrogenation catalysts due to its good catalytic effect and low cost, and is widely used. However, Ni-based catalysts have poor stability and are prone to deactivation. In practical applications, the synergistic effect generated by bimetallic catalysts is often utilized. Ru has good hydrogenation activity and can transfer electrons to Ni, improving the ability to adsorb hydrogen and enhance hydrogenolysis performance. Chang Jie (CN113231075A) used RuNi / DMO, a hydrotalcite-based oxide supported on ruthenium and nickel, to catalyze the hydrogenolysis of lignin. After 8 hours of reaction at 280℃ and 4MPaH2, the yield of cyclohexanol products reached 8.47 wt.%. Li Zhanku (CN114029070A) prepared a supported highly dispersed NiRu alloy catalyst using NiRuAl hydrotalcite as a precursor through calcination and reduction. The Ni and Ru accounted for 20%–40% and 1%–5% of the catalyst, respectively. This highly dispersed NiRu alloy catalyst can selectively and actively break the aryl ether bonds in lignin and its model compounds under mild conditions. Ni in hydrogenation catalysts... 0 The coexistence of H2 and NiO can have a synergistic effect. 0 Surface adsorption and activation, the substrate undergoes hydrogenation reaction on the NiO surface (Efficient and low-cost Ni-NiO / Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide. Chemical Engineering Journal, 2024).
[0004] CN118459321A discloses a method for selectively hydrogenating lignin to obtain C6 monophenols, comprising: using the hydrogen-containing functional groups of lignin itself as the hydrogen source for reductive depolymerization in an aqueous solvent system, and selectively converting lignin to C6 monophenols in a one-pot process. Specifically, this technology uses hydroxyapatite as a support, loaded with a certain amount of metal. Lignin, catalyst, and water are placed together in a reactor, purged and sealed with nitrogen gas, and subjected to hydrogenolysis at a specific temperature and time. After the reaction, the mixture is extracted with ethyl acetate in three portions to remove the lignin monomers, ultimately yielding C6 monophenols (phenol, guaiacol, and 2,6-dimethoxyphenol) with a selectivity as high as 74.4%. The catalysts used include one or more combinations of hydroxyapatite, silica, hydrotalcite, magnesium oxide, metal oxides, and metal nitride supports. Although the catalyst used in this technology can achieve high selectivity for C6 monophenols in the hydrogenolysis reaction, it is prepared by a one-pot method. The disordered assembly of the support material limits the subsequent loading of active metal elements on the catalyst. Furthermore, during the catalytic reaction, the catalyst can only exert its catalytic effect on the active sites on the outer surface of the catalyst, which further limits the catalytic efficiency of the catalyst.
[0005] CN115041190A discloses the preparation and application of a highly dispersed Ni-Ru / Al2O3 catalyst with topological transformation in hydrotalcite. This catalyst uses NiAl hydrotalcite as a precursor, introduces Ru exogenously, and prepares a highly dispersed Ni-Ru / Al2O3 catalyst through topological transformation and in-situ reduction. This catalyst exhibits excellent catalytic performance in the hydrogenolysis of lignin and its model compounds, selectively and actively breaking aryl ether bonds in lignin and its model compounds under mild conditions, significantly outperforming commercial Ru / C catalysts. While the catalyst achieves excellent reaction performance in hydrogenolysis, its preparation process using a one-step method for the Ni-Al hydrotalcite support is problematic. During this process, Ni agglomeration easily occurs, making it difficult to maintain high Ni dispersion in the support. Furthermore, whether the synergistic effect between Ni and Ru can be fully utilized in the subsequent Ru loading process requires further investigation.
[0006] CN113231075A discloses a method for depolymerizing lignin into cyclohexanol compounds using RuNi supported on hydrotalcite oxide. This technique combines the lamellar structure and weak basicity of DMO, using Ru and Ni as active centers for lignin hydrogenolysis. The Ru / DMO method exhibits extremely high activity in lignin hydrogenation systems, achieving a cyclohexanol yield of 8.47 wt% under conditions of 280℃, 4 MPa H2, 40 mL water, and 8 hours. Furthermore, the yield did not significantly decrease after three catalyst reuses. However, the disclosed DMO preparation scheme employs traditional co-precipitation for support preparation. The assembly of the support material in this process is affected by various preparation conditions, making it difficult to guarantee the repeatability of the structural properties of the resulting support.
[0007] CN112341312A discloses a method for selective hydrogenolysis of lignin to prepare cyclohexanol and its derivatives. This method involves mixing ruthenium-supported hydrotalcite oxide, lignin, and a solvent, reacting the mixture at 200–280°C and H2 pressure of 1–5 MPa for 2–10 hours, followed by solid-liquid separation to obtain a product mixture containing cyclohexanol and its derivatives. The preparation process of the hydrotalcite oxide involves uniformly mixing Mg(NO3)2·6H2O and Al(NO3)3·9H2O with water, then adding the mixture to a Na2CO3 solution at a certain rate, while simultaneously adjusting the pH of the system to 10 using NaOH solution. The mixture is then subjected to aging, washing, and calcination steps. Although the catalyst used in this technology achieves high product selectivity during the hydrogenolysis reaction, the catalyst support is prepared by chemical precipitation. The disordered assembly of the support material limits the subsequent loading of active metal elements into the prepared catalyst. Furthermore, during the catalytic reaction, the catalyst can only exert its catalytic effect at the active sites on its outer surface, further limiting the catalytic efficiency. Summary of the Invention
[0008] The purpose of this invention is to provide a Ru-Ni / NiO-MMO catalyst, its preparation, and its application. The Ru-Ni / NiO-MMO catalyst prepared by this invention possesses excellent active element loading, and its rich textural structure enhances the diffusion performance of lignin feedstock molecules, thereby further improving the catalytic efficiency of the active elements. Applying the catalyst prepared by this invention to the lignin hydrogenolysis reaction process can achieve a higher lignin conversion rate, with a liquid-phase product yield exceeding 75% and a monomeric phenol selectivity of over 45% in the product.
[0009] To achieve the above objectives, the present invention adopts the following technical solution:
[0010] The first aspect of this invention provides a method for preparing a Ru-Ni / NiO-MMO catalyst, wherein the preparation method includes the following steps:
[0011] 1) Ni(NO3)2·6H2O, Mg(NO3)2·6H2O, metal nitrate A, and steric hindrance B are dissolved in a solvent, wherein the metal nitrate A is selected from at least one of Fe(NO3)3·9H2O, Al(NO3)3·9H2O, and Co(NO3)3·6H2O; the pH of the solution is adjusted to 8-12 and then a hydrothermal crystallization reaction is carried out; after the reaction is completed, the temperature is lowered to room temperature, the solid is separated, washed, dried, and ground into powder to obtain the Ni-based LDHs precursor;
[0012] 2) The Ni-based LDHs precursor was calcined in air and then reduced in a H2 / N2 mixture to obtain NiMg. 1-4 A 1-1.5 O y , where y: 3.0~6.0;
[0013] 3) The NiMg 1-4 A 1-1.5 O y The Ru-Ni / NiO-MMO precursor was obtained by immersing the precursor in an aqueous solution of Ru(CH3COO)3 for a predetermined time and then drying it.
[0014] 4) The Ru-Ni / NiO-MMO precursor was calcined in an N2 atmosphere and then reduced in an H2 / N2 mixture to obtain Ru-Ni / NiO-MMO.
[0015] The preparation method of this invention mainly includes: 1) preparation of Ni-based LDHs precursor, 2) NiMg 1-4 A 1-1.5 O yThe preparation of the precursors of Ru-Ni / NiO-MMO is described in section 3, and section 4. The preparation of Ru-Ni / NiO-MMO is also described. In the pre-synthesis process of the hydrotalcite (LDHs) support material, the steric hindrance agent B is introduced into the synthesis formulation. The steric hindrance agent guides the formation of layered hydrotalcite materials. Simultaneously, the pH of the synthesis system is adjusted during the synthesis process to change the charge properties around the metal cations, thereby controlling the growth of the support and the loading of the active element nickel on the support, achieving uniform loading of nickel on the support. Furthermore, to further enhance the catalytic activity of nickel, the present invention introduces a Ru co-catalytic component. To enhance the dispersion of Ru on the support and ensure its co-catalytic effect on the active metal element Ni, the present invention prepares an aqueous solution of Ru(CH3COO)3. Through the non-polarization interaction between the Ru(CH3COO)3 components, the aggregation of Ru during the loading process is reduced, ensuring its highly dispersed loading on NiMg. 1-4 A 1-1.5 O y On the surface.
[0016] The following provides a detailed explanation of each step:
[0017] Step 1) Preparation of Ni-based LDHs precursors:
[0018] Ni(NO3)2·6H2O, Mg(NO3)2·6H2O, metal nitrate A, and steric hindrance B are dissolved in a solvent. The metal nitrate A is selected from at least one of Fe(NO3)3·9H2O, Al(NO3)3·9H2O, and Co(NO3)3·6H2O. The pH of the solution is adjusted to 8-12, and then a hydrothermal crystallization reaction is carried out. After the reaction is completed, the temperature is lowered to room temperature, the solid is separated, washed, dried, and ground into powder to obtain the Ni-based LDHs precursor.
[0019] This step mainly involves hydrolysis, where the raw materials react to produce NiMg. 1-4 A 1-1.5 (OH)2(NO3) 5-11 (1-8)H2O, after hydrothermal preparation, the product includes not only LDHs material, but also the steric hindrance agent B used in the synthesis. Secondly, in order to remove the water of crystallization in the LDHs material, the product needs to be calcined.
[0020] In step 1), preferably, the molar ratio of Ni(NO3)2·6H2O, Mg(NO3)2·6H2O and metal nitrate A is 1:(1~4):(1~1.5).
[0021] In step 1), preferably, the steric hindrance agent B is selected from at least one of hexadecyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium chloride (DTAC), sodium dodecylbenzenesulfonate (SDBS), sodium dodecyl sulfate (SDS), F127 (PEO-PPO-PEO triblock copolymer), and P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, PEO-PPO-PEO).
[0022] In step 1), preferably, the amount of steric hindrance B added is 1 to 2 times the mass of metal nitrate A.
[0023] In step 1), preferably, the solvent is an ethanol-water mixture. More preferably, the volume ratio of ethanol in the ethanol-water mixture is (5-30) vol.%. Even more preferably, the molar ratio of the metal nitrate to water in the reaction system is 1:(30-100), wherein the metal nitrate includes Ni(NO3)2·6H2O, Mg(NO3)2·6H2O, and metal nitrate A.
[0024] In step 1), preferably, NaOH solution is used to adjust the pH value of the solution. The specific concentration of the NaOH solution can be, for example, 2 mol / L, etc., but the present invention does not limit this.
[0025] In step 1), preferably, the temperature of the hydrothermal crystallization reaction is 150-200°C and the time is 10-24 hours.
[0026] Step 2) NiMg 1-4 A 1-1.5 O y Preparation:
[0027] The Ni-based LDHs precursor was calcined in air and then reduced in an H2 / N2 mixture to obtain NiMg. 1-4 A 1-1.5 O y .
[0028] The chemical formula of the product after calcination is NiMg 1-4 A 1-1.5 O x Where x: 3.5~6.5; the chemical formula of the reduced product is NiMg 1-4 A 1-1.5 O y Where y: 3.0~6.0. This invention employs a two-step reduction. The defects generated after the reduction of Ni element in the first step are beneficial to the loading of Ru element in the second step. If a co-reduction is used, it is impossible to guarantee that Ru element maintains a high degree of dispersion. Secondly, it is not easy to control the aggregation of Ni and Ru elements themselves during the co-reduction process.
[0029] In step 2), preferably, the calcination temperature in the air atmosphere is 600-1000℃ and the time is 6-12h.
[0030] In step 2), preferably, the volume ratio of H2 to N2 in the H2 / N2 mixture is 1:(1~9); the flow rate of the H2 / N2 mixture is 50~100mL / min; the reduction temperature is 400~800℃; and the reduction time is 4~10h.
[0031] Step 3) Preparation of Ru-Ni / NiO-MMO precursor:
[0032] The NiMg 1-4 A 1-1.5 O y The Ru-Ni / NiO-MMO precursor was obtained by immersing the precursor in an aqueous solution of Ru(CH3COO)3 for a predetermined time and then drying it.
[0033] In this invention, Ni-based hydrotalcite is first prepared, then reduced to obtain zero-valent Ni, followed by Ru loading and then further reduction of Ru. This method facilitates the control of maintaining a high degree of dispersion between the active metal element Ni and the co-catalyst active component Ru, thereby achieving a superior catalytic effect. However, if Ni and Ru are added together during the initial preparation of the hydrotalcite, the catalytic effect of the prepared catalyst is not as good as that of the catalyst obtained by the method of this invention.
[0034] In the preparation method of this invention, Ru(CH3COO)3 is used when Ru is supported, mainly utilizing CH3COO - The charge repulsion between functional groups prevents Ru from agglomerating during loading, ensuring Ru dispersion and thus fully leveraging its co-catalytic effect.
[0035] In step 3), preferably, the concentration of the Ru(CH3COO)3 aqueous solution is (0.5–10) wt.%, more preferably (2–10) wt.%.
[0036] In step 3), preferably, the Ru(CH3COO)3 aqueous solution reacts with NiMg 1-4 A 1-1.5 O y The mass ratio is (1~10):1.
[0037] In step 3), preferably, the soaking time is 1 to 24 hours.
[0038] Step 4) Preparation of Ru-Ni / NiO-MMO:
[0039] The Ru-Ni / NiO-MMO precursor was calcined in an N2 atmosphere and then reduced in an H2 / N2 mixture to obtain Ru-Ni / NiO-MMO.
[0040] In step 4), calcination in a nitrogen atmosphere can prevent sintering during the high-temperature air calcination of Ru, and at the same time, it can ensure that the alkaline oxides obtained by calcination retain their layered structure to the greatest extent.
[0041] In step 4), preferably, the calcination temperature of the Ru-Ni / NiO-MMO precursor is 300-600℃, and the calcination time is 2-8h.
[0042] In step 4), preferably, the volume ratio of H2 to N2 in the H2 / N2 mixture is 1:(1~9), the flow rate of the H2 / N2 mixture is 50~100mL / min, the reduction temperature is 400~800℃, and the reduction time is 2~10h.
[0043] A second aspect of the present invention provides a Ru-Ni / NiO-MMO catalyst, which is obtained by any of the above preparation methods.
[0044] A third aspect of the present invention provides a method for applying the Ru-Ni / NiO-MMO catalyst described above in the catalytic hydrogenolysis of lignin, comprising the following steps:
[0045] Lignin and the Ru-Ni / NiO-MMO catalyst were added to a hydrogen-donating solvent and depolymerized at 200–350 °C. After the reaction was completed, the mixture was cooled to room temperature and filtered. The hydrogen-donating solvent was removed from the liquid phase. Then, hydrochloric acid solution was added for acidification, followed by extraction with ethyl acetate. The upper liquid was dried and the ethyl acetate was removed to obtain the liquid product.
[0046] In the lignin depolymerization method of the present invention, the yield of the liquid phase product after lignin depolymerization is greater than 75%, and the liquid phase product contains phenols, guaiacol, syringol and their corresponding derivatives, wherein the monomer phenol selectivity is greater than 45%.
[0047] Preferably, the lignin is an organic solvent lignin or lignin sulfonate.
[0048] Preferably, the mass ratio of lignin to Ru-Ni / NiO-MMO catalyst is 1:(0.5-2).
[0049] Preferably, the hydrogen-donating solvent is selected from at least one of ethanol, isopropanol, n-butanol, sec-butanol, and tert-butanol.
[0050] Preferably, the depolymerization reaction takes 2 to 12 hours.
[0051] Preferably, the acidification is carried out to pH=1.
[0052] The beneficial effects of this invention include:
[0053] (1) Based on hydrotalcite-based solid alkali oxide, this invention combines multiple active sites Ru, Ni, NiO and MMO through reduction and loading to construct a multi-active site Ru-Ni / NiO-MMO, which is simple to prepare.
[0054] (2) The present invention utilizes the prepared Ru-Ni / NiO-MMO to catalyze the hydrogenolysis of lignin, which has a high lignin conversion rate and a liquid phase product yield of over 75%. The main products are cyclohexanol and its derivatives, phenol and its derivatives, guaiacol and its derivatives, syringol and its derivatives, etc., with a monomer phenol selectivity of over 45%. Attached Figure Description
[0055] Figure 1 This is the XRD pattern of hydrotalcite NiMgCo-LDHs in Example 1.
[0056] Figure 2 This is a SEM image of hydrotalcite NiMgCo-LDHs from Example 1.
[0057] Figure 3 It is the catalytically active component NiMg3CoO in Example 1 y XRD pattern.
[0058] Figure 4 It is the catalytically active component NiMg3CoO in Example 1 y SEM image. Detailed Implementation
[0059] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments, further clarifies the invention. Those skilled in the art should understand that the specific descriptions below are illustrative rather than restrictive, and should not be construed as limiting the scope of protection of the present invention.
[0060] All numerical specifications in this invention (e.g., temperature, time, concentration, and weight, including ranges for each) are generally approximate values that may be changed (+) or (-) in increments of 0.1 or 1.0. All numerical specifications are to be understood as being preceded by the term "about".
[0061] Example 1:
[0062] This embodiment prepares a Ru-Ni / NiO-MMO catalyst and uses it in the catalytic hydrogenolysis of lignin, including the following steps:
[0063] 1.454 g Ni(NO3)2·6H2O, 3.846 g Mg(NO3)2·6H2O, 1.455 g Co(NO3)2·6H2O, and 2.181 g CTAB were weighed and added to a polytetrafluoroethylene reactor. 50 mL of an ethanol-water solution (15 vol.%) was added to completely dissolve the metal nitrates and CTAB. The pH of the solution was adjusted to 9.5 with 2 mol / L NaOH solution, and then hydrothermally crystallized at 180℃ for 24 h. After crystallization, the solution was cooled to room temperature, washed with deionized water, and centrifuged until the supernatant was neutral. The resulting product was dried in a vacuum drying oven and ground into powder, which is the Ni-based LDH precursor.
[0064] Figure 1 and Figure 2 The images shown are the XRD and SEM images of NiMgCo-LDHs, respectively. Figure 1 As can be seen from the data, the NiMgCo-LDHs prepared in Example 1 exhibited characteristic XRD diffraction peaks of hydrotalcite at diffraction angles of 2θ = 10-12°, 20-25°, 30-35°, and 60-65°, and the characteristic peaks were relatively sharp, indicating that its crystallinity was high. Figure 2 It can be seen that it has a layered structure, indicating that the NiMgCo-LDHs prepared in this invention has a hydrotalcite structure.
[0065] The obtained Ni-based LDHs precursor was calcined at 800℃ for 6 hours in air to obtain solid alkali oxide NiMg3CoO. 5.5 Then, in the H2 / N2 mixture (V H2 :V N2 Reduction at 500℃ for 4 h in a 1:4 ratio with H2 / N2 mixed gas flow rate of 50 mL / min yielded the catalytically active component NiMg3CoO. y , where y is 5.
[0066] Figure 3 The solid alkali oxide NiMg3CoO obtained after calcination and hydrogen reduction y The XRD characterization diagram shows that there are characteristic diffraction peaks of elemental nickel at diffraction angles of 2θ = 44.5° and 76.4°. The intensity of the characteristic peaks is low, indicating that the Ni element particles are small and highly dispersed. Figure 4 It is an alkaline oxide NiMg3CoO y The SEM characterization image shows that after calcination and reduction, the basic oxide still maintains a layered structure. Due to the high-temperature decomposition of the steric hindrance, a porous structure appears on the basic oxide. The appearance of this structure can promote the contact between the catalytic active site and the reactant phase, thereby further improving the catalytic efficiency of the catalyst.
[0067] Mix 2 mL of 2 wt.% Ru(CH3COO)3 aqueous solution with 1 g of catalytically active component NiMgCoO y The mixture was stirred and stirred until homogeneous, then impregnated for 3 hours. The sample was then dried using a vacuum drying method at 40℃, an absolute pressure of 130Pa, and a vacuum drying time of 8 hours to obtain the Ru-Ni / NiO-MMO precursor. This precursor was then calcined at 500℃ in a N2 atmosphere for 4 hours, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 600℃ for 4 hours in a mixture of 1:4 (NiO = 1:4) with a H2 / N2 mixed gas flow rate of 50 mL / min.
[0068] 1 g of organic solvent lignin and 1 g of Ru-Ni / NiO-MMO were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 270 °C for 4 h. After the reaction was completed, the mixture was cooled to room temperature, and the liquid-solid mixture was filtered to separate the solid and liquid phases. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The supernatant was dried with anhydrous MgSO4, and the ethyl acetate was removed by rotary evaporation to obtain 0.769 g of liquid product, which represents a liquid phase product yield of 76.9%. The main products were cyclohexanol and its derivatives, phenol and its derivatives, guaiacol and its derivatives, syringol and its derivatives, etc., with a monomeric phenol selectivity of 48.7%.
[0069] Example 2:
[0070] This embodiment prepares a Ru-Ni / NiO-MMO catalyst and uses it in the catalytic hydrogenolysis of lignin, including the following steps:
[0071] 1.454 g Ni(NO3)2·6H2O, 3.846 g Mg(NO3)2·6H2O, 3.029 g Fe(NO3)3·9H2O, and 4.36 g F127 were weighed and added to a polytetrafluoroethylene reactor. 60 mL of an ethanol-water solution (15 vol.%) was added to completely dissolve the metal nitrates and F127. The pH of the solution was adjusted to 10 with 2 mol / L NaOH solution, and then hydrothermally crystallized at 160 °C for 24 h. After crystallization, the mixture was cooled to room temperature, washed with deionized water, and centrifuged until the supernatant was neutral. The resulting product was dried in a vacuum drying oven and ground into powder, which is the Ni-based LDH precursor.
[0072] The obtained Ni-based LDHs precursor was calcined at 800℃ for 6 h in air to obtain solid alkali oxide NiMg3Fe. 1.5 O 5.5Then, in the H2 / N2 mixture (V H2 :V N2 Reduction at 500℃ for 4 h in a 1:4 ratio with H2 / N2 mixed gas flow rate of 50 mL / min yielded the catalytically active component NiMg3Fe. 1.5 O y , where y is 4.8.
[0073] Mix 3 mL of 2 wt.% Ru(CH3COO)3 aqueous solution with 1 g of catalytically active component NiMg3Fe 1.5 O y The mixture was stirred and stirred until homogeneous, then impregnated for 3 hours. The sample was then dried using a vacuum drying method at 40℃, an absolute pressure of 130Pa, and a vacuum drying time of 8 hours to obtain the Ru-Ni / NiO-MMO precursor. This precursor was then calcined at 500℃ in a N2 atmosphere for 4 hours, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 600℃ for 4 hours in a mixture of 1:4 (NiO = 1:4) with a H2 / N2 mixed gas flow rate of 50 mL / min.
[0074] 1 g of sodium lignosulfonate and 0.5 g of Ru-Ni / NiO-MMO catalyst were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 250 °C for 4 h. After the reaction, the mixture was cooled to room temperature, and the liquid-solid mixture was filtered and separated. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The upper liquid was dried with anhydrous MgSO4, and the ethyl acetate was removed by rotary evaporation to obtain 0.764 g of liquid product, i.e., the liquid phase product yield reached 76.4%, with a phenol monomer selectivity of 51.2%.
[0075] Example 3:
[0076] This embodiment prepares a Ru-Ni / NiO-MMO catalyst and uses it in the catalytic hydrogenolysis of lignin, including the following steps:
[0077] 1.454 g Ni(NO3)2·6H2O, 3.846 g Mg(NO3)2·6H2O, 1.876 g Al(NO3)3·9H2O, and 2.181 g SDBS were weighed and added to a polytetrafluoroethylene reactor. 50 mL of an ethanol-water solution (15 vol.%) was added to completely dissolve the metal nitrates and SDBS. The pH of the solution was adjusted to 12 with 2 mol / L NaOH solution, and then hydrothermally crystallized at 180 °C for 24 h. After crystallization, the mixture was cooled to room temperature, washed with deionized water, and centrifuged until the supernatant was neutral. The resulting product was dried in a vacuum drying oven and ground into powder, which is the Ni-based LDHs precursor.
[0078] The obtained Ni-based LDHs precursor was calcined at 1000℃ for 6 hours in air to obtain solid alkali oxide NiMg3AlO. x Then, in the H2 / N2 mixture (V H2 :V N2 Reduction was carried out at 500℃ for 4 hours in a 1:4 ratio (H2 / N2 mixed gas flow rate was 100 mL / min), with the catalytically active component being NiMg3AlO4. y , where y is 5.3.
[0079] 2 mL of 2 wt.% Ru(CH3COO)3 aqueous solution was mixed with 1 g of catalytically active component NiMg3AlO y The mixture was stirred and stirred until homogeneous, then impregnated for 3 hours. The sample was then dried using a vacuum drying method at 60℃, an absolute pressure of 100Pa, and a vacuum drying time of 5 hours to obtain the Ru-Ni / NiO-MMO precursor. This precursor was then calcined at 600℃ in a N2 atmosphere for 4 hours, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 800℃ for 4 hours in a mixture of 1:4 (H2 / N2) with a gas flow rate of 100 mL / min.
[0080] 1 g of organic solvent lignin and 0.5 g of Ru-Ni / NiO-MMO catalyst were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 270 °C for 4 h. After the reaction, the mixture was cooled to room temperature, and the liquid-solid mixture was filtered to separate the solid and liquid phases. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The supernatant was dried with anhydrous MgSO4, and the ethyl acetate was removed by rotary evaporation to obtain 0.759 g of liquid product, i.e., the liquid phase product yield reached 75.9%, with a phenol monomer selectivity of 53.4%.
[0081] Example 4:
[0082] This embodiment prepares a Ru-Ni / NiO-MMO catalyst and uses it in the catalytic hydrogenolysis of lignin, including the following steps:
[0083] 1.454 g Ni(NO3)2·6H2O, 3.846 g Mg(NO3)2·6H2O, 0.728 g Co(NO3)2·6H2O, 1.01 g Fe(NO3)3·9H2O, and 2.908 g P123 were weighed and added to a polytetrafluoroethylene reactor. 60 mL of an ethanol-water solution (15 vol.%) was added to completely dissolve the metal nitrates and P123. The pH of the solution was adjusted to 10 with 2 mol / L NaOH solution, and then hydrothermally crystallized at 180 °C for 24 h. After crystallization, the mixture was cooled to room temperature, washed with deionized water, and centrifuged until the supernatant was neutral. The resulting product was dried in a vacuum drying oven and ground into powder, which is the Ni-based LDH precursor.
[0084] The obtained Ni-based LDHs precursor was calcined at 800℃ for 6 h in air to obtain solid alkali oxide NiMgCo. 0.5 Fe 0.5 O x Then, in the H2 / N2 mixture (V H2 :V N2 Reduction was carried out at 500℃ for 4 hours in a 1:4 ratio (H2 / N2 mixed gas flow rate was 100 mL / min), with the catalytically active component being NiMg3Co. 0.5 Fe 0.5 O y , where y is 5.
[0085] Add 3 mL of 2 wt.% Ru(CH3COO)3 solution and 1 g of the catalytically active component NiMg3Co 0.5 Fe 0.5 O y The mixture was stirred and stirred until homogeneous, then impregnated for 3 hours. The sample was then dried using a vacuum drying method at 60℃, an absolute pressure of 100Pa, and a vacuum drying time of 5 hours to obtain the Ru-Ni / NiO-MMO precursor. This precursor was then calcined at 600℃ in a N2 atmosphere for 4 hours, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 800℃ for 6 hours in a mixture of 1:9 (NiO = 1:9) with a H2 / N2 mixed gas flow rate of 100 mL / min.
[0086] 1 g of organic solvent lignin and 2 g of Ru-Ni / NiO-MMO catalyst were added to 50 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 250 °C for 4 h. After the reaction was completed and cooled to room temperature, the liquid-solid mixture was filtered and separated. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The upper liquid was dried with anhydrous MgSO4, and the ethyl acetate was removed by rotary evaporation to obtain 0.781 g of liquid product, i.e., the liquid phase product yield reached 78.1%, with a phenol monomer selectivity of 50.9%.
[0087] Example 5:
[0088] This embodiment prepares a Ru-Ni / NiO-MMO catalyst and uses it in the catalytic hydrogenolysis of lignin, including the following steps:
[0089] 1.454 g Ni(NO3)2·6H2O, 5.128 g Mg(NO3)2·6H2O, 2.183 g Co(NO3)2·6H2O, and 3.272 g CTAB were weighed and added to a polytetrafluoroethylene reactor. 50 mL of an ethanol-water solution (15 vol.%) was added to completely dissolve the metal nitrates and CTAB. The pH of the solution was adjusted to 9.5 with 2 mol / L NaOH solution, and then hydrothermally crystallized at 200℃ for 10 h. After crystallization, the solution was cooled to room temperature, washed with deionized water, and centrifuged until the supernatant was neutral. The resulting product was dried in a vacuum drying oven and ground into powder, which is the Ni-based LDH precursor.
[0090] The obtained Ni-based LDHs precursor was calcined at 600℃ for 12 h in air to obtain solid alkali oxide NiMg4Co. 1.5 O x Then, in the H2 / N2 mixture (V H2 :V N2 The catalytically active component NiMg4Co was obtained by reduction at 400℃ for 10 h in a 1:4 ratio with a H2 / N2 mixed gas flow rate of 50 mL / min. 1.5 O y , where y is 6.
[0091] 2 mL of 2 wt.% Ru(CH3COO)3 solution was mixed with 1 g of the catalytically active component NiMg4Co. 1.5 O yThe mixture was stirred and stirred until homogeneous, then impregnated for 3 hours. The sample was then dried using a vacuum drying method at 40℃, an absolute pressure of 130Pa, and a vacuum drying time of 8 hours to obtain the Ru-Ni / NiO-MMO precursor. This precursor was then calcined at 300℃ in a N2 atmosphere for 8 hours, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 500℃ for 2 hours in a mixture of 1:4 (NiO = 1:4) with a H2 / N2 mixed gas flow rate of 50 mL / min.
[0092] 1 g of organic solvent lignin and 1 g of Ru-Ni / NiO-MMO catalyst were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 250 °C for 4 h. After the reaction, the mixture was cooled to room temperature, and the liquid-solid mixture was filtered and separated. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The upper liquid was dried with anhydrous MgSO4, and then the ethyl acetate was removed by rotary evaporation to obtain 0.713 g of liquid product, i.e., the liquid phase product yield reached 71.3%. The main products were cyclohexanol and its derivatives, phenol and its derivatives, guaiacol and its derivatives, syringol and its derivatives, etc., with a monomeric phenol selectivity of 50.1%.
[0093] Example 6:
[0094] This embodiment prepares a Ru-Ni / NiO-MMO catalyst and uses it in the catalytic hydrogenolysis of lignin, including the following steps:
[0095] 1.454 g Ni(NO3)2·6H2O, 1.282 g Mg(NO3)2·6H2O, 1.455 g Co(NO3)2·6H2O, and 2.91 g CTAB were weighed and added to a polytetrafluoroethylene reactor. 50 mL of an ethanol-water solution (15 vol.%) was added to completely dissolve the metal nitrates and CTAB. The pH of the solution was adjusted to 11 with 2 mol / L NaOH solution, and then hydrothermally crystallized at 150 °C for 30 h. After crystallization, the solution was cooled to room temperature, washed with deionized water, and centrifuged until the supernatant was neutral. The resulting product was dried in a vacuum drying oven and ground into powder, which is the Ni-based LDH precursor.
[0096] The obtained Ni-based LDHs precursor was calcined at 600℃ for 12 h in air to obtain solid alkali oxide NiMgCoO. x Then, in the H2 / N2 mixture (V H2 :V N2The catalyst-active component NiMg3CoO was obtained by reduction at 400℃ for 10 h in a 1:4 ratio with a H2 / N2 mixed gas flow rate of 50 mL / min. y , where y is 4.1.
[0097] Mix 2 mL of 2 wt.% Ru(CH3COO)3 solution with 1 g of the catalytically active component NiMg3CoO y The samples were mixed, stirred thoroughly, and impregnated for 3 hours. Vacuum drying was then performed at 40℃, with an absolute pressure of 130 Pa, for 8 hours to obtain the Ru-Ni / NiO-MMO precursor. This precursor was then calcined at 500℃ in a N2 atmosphere for 2 hours, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 400℃ for 10 h in a mixture of 1:4 and H2 / N2 at a gas flow rate of 50 mL / min.
[0098] 1 g of organic solvent lignin and 1 g of Ru-Ni / NiO-MMO catalyst were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 350 °C for 4 h. After the reaction, the mixture was cooled to room temperature, and the liquid-solid mixture was filtered and separated. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The upper liquid was dried with anhydrous MgSO4, and the ethyl acetate was removed by rotary evaporation to obtain 0.784 g of liquid product, i.e., the liquid phase product yield reached 78.4%. The main products were cyclohexanol and its derivatives, phenol and its derivatives, guaiacol and its derivatives, syringol and its derivatives, etc., with a monomeric phenol selectivity of 53.4%.
[0099] Example 7:
[0100] This embodiment prepares a Ru-Ni / NiO-MMO catalyst and uses it in the catalytic hydrogenolysis of lignin, including the following steps:
[0101] Weigh 1.454g Ni(NO3)2·6H2O, 3.846g Mg(NO3)2·6H2O, 1.455g Co(NO3)2·6H2O, and 2.91g F127 and add them to a polytetrafluoroethylene reactor. Add 50mL of ethanol-water solution (ethanol content 15 vol.%) to completely dissolve the metal nitrates and CTAB. Adjust the pH of the solution to 9.5 with 2mol / L NaOH solution, and then perform hydrothermal crystallization at 200℃ for 12h. After crystallization, cool to room temperature, wash with deionized water, and centrifuge until the supernatant is neutral. Dry the obtained product in a vacuum drying oven and grind it into powder, which is the Ni-based LDHs precursor.
[0102] The obtained Ni-based LDHs precursor was calcined at 800℃ for 6 hours in air to obtain solid alkali oxide NiMgCoO. x Then, in the H2 / N2 mixture (V H2 :V N2 Reduction at 800℃ for 6 h in a 1:9 ratio with H2 / N2 mixed gas flow rate of 100 mL / min yielded the catalytically active component NiMg3CoO. y , where y is 4.8.
[0103] Mix 2 mL of 2 wt.% Ru(CH3COO)3 solution with 1 g of the catalytically active component NiMg3CoO y The mixture was stirred and stirred until homogeneous, then impregnated for 3 hours. The sample was then dried using a vacuum drying method at 60℃, an absolute pressure of 100Pa, and a vacuum drying time of 5 hours to obtain the Ru-Ni / NiO-MMO precursor. This precursor was then calcined at 500℃ in a N2 atmosphere for 4 hours, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 400℃ for 10 h in a mixture of 1:4 and H2 / N2 at a gas flow rate of 100 mL / min.
[0104] 1 g of organic solvent lignin and 1 g of Ru-Ni / NiO-MMO catalyst were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 270 °C for 4 h. After the reaction, the mixture was cooled to room temperature, and the liquid-solid mixture was filtered and separated. The liquid phase was used to remove isopropanol by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The upper liquid was dried with anhydrous MgSO4, and then the ethyl acetate was removed by rotary evaporation to obtain 0.76 g of liquid product, i.e., the liquid phase product yield reached 76.0%. The main products were cyclohexanol and its derivatives, phenol and its derivatives, guaiacol and its derivatives, syringol and its derivatives, etc., with a monomeric phenol selectivity of 49.4%.
[0105] Comparative Example 1:
[0106] Solid alkali oxide NiMg3CoO was prepared according to the method in Example 1. 5.5 Without initial reduction, 1g of solid alkali oxide was directly mixed with 2mL of 2wt.% Ru(CH3COO)3 aqueous solution, stirred evenly, and impregnated for 3h. The sample was then dried using a vacuum drying method at 40℃, 130Pa absolute pressure, and 8h to obtain the Ru-NiO-MMO precursor. This precursor was then calcined at 500℃ in a N2 atmosphere for 4h, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 600℃ for 4 hours in a mixture of 1:4 (NiO = 1:4) with a H2 / N2 mixed gas flow rate of 50 mL / min.
[0107] 1 g of organic solvent lignin and 1 g of Ru-Ni / NiO-MMO were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 270 °C for 4 h. After the reaction was completed and cooled to room temperature, the liquid-solid mixture was filtered and separated. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The supernatant was dried with anhydrous MgSO4, and the ethyl acetate was removed by rotary evaporation to obtain 0.56 g of liquid product, i.e., the liquid phase product yield reached 56.0%, and the selectivity of the monomer phenol in the product was 43.5%.
[0108] Comparative Example 2:
[0109] Solid alkali oxide NiMg3FeO was prepared according to the method in Example 2. 5.5Without initial reduction, 1g of solid alkali oxide was directly mixed with 3mL of 2wt.% Ru(CH3COO)3 aqueous solution, stirred evenly, impregnated for 3h, and dried. The sample was then dried using a vacuum drying method at 40℃, 130Pa absolute pressure, and 8h to obtain the Ru-NiO-MMO precursor. This precursor was then calcined at 500℃ in a N2 atmosphere for 4h, followed by calcination in a H2 / N2 mixed gas (V... H2 :V N2 The Ru-Ni / NiO-MMO catalyst was obtained by reducing the catalyst at 600℃ for 4 hours in a mixture of 1:4 (NiO = 1:4) with a H2 / N2 mixed gas flow rate of 50 mL / min.
[0110] 1 g of sodium lignosulfonate and 0.5 g of Ru-Ni / NiO-MMO catalyst were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature and high-pressure reactor at 250 °C for 4 h. After the reaction, the mixture was cooled to room temperature, and the liquid-solid mixture was filtered to separate the solids. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The supernatant was dried with anhydrous MgSO4, and the ethyl acetate was removed by rotary evaporation to obtain 0.657 g of liquid product, i.e., the liquid phase product yield reached 58.7%, with a phenol monomer selectivity of 46.3%.
[0111] Comparative Example 3:
[0112] The catalytically active component NiMg3CoO was prepared according to the method in Example 1. y The prepared catalytically active component was directly applied to the catalytic depolymerization reaction. The reaction steps and reaction conditions were the same as in Example 1. The yield of the liquid phase product was 60.3%, and the selectivity of the monomer phenol was 40.8%.
[0113] Comparative Example 4:
[0114] The Ru-Ni / NiO-MMO catalyst was prepared according to the method in Example 1, except that 1g of the catalytically active component NiMg3CoO was used. y The sample was mixed with 2 mL of 0.5 wt.% Ru(CH3COO)3 solution, stirred until homogeneous, and impregnated for 3 h. The sample was then dried under vacuum at 40 °C, 130 Pa absolute pressure, and for 8 h to obtain the Ru-Ni / NiO-MMO precursor. This precursor was then calcined at 500 °C in a N2 atmosphere for 4 h, followed by calcination under a H2 / N2 mixed gas (V... H2 :V N2The Ru-Ni / NiO-MMO catalyst was obtained by reduction at 600℃ for 4 h in a 1:4 ratio with a H2 / N2 mixed gas flow rate of 50 mL / min. The yield of the obtained liquid phase product was 66.3%, with a monomer phenol selectivity of 46.6%.
[0115] Comparative Example 5:
[0116] The Ru-Ni / NiO-MMO catalyst was prepared according to the method in Example 1, except that 0.7275 g of CTAB was used in the preparation of the Ni-based LDHs precursor. 1 g of organic solvent lignin and 1 g of Ru-Ni / NiO-MMO were added to 40 mL of isopropanol. After purging with N2 for 20 min, a depolymerization reaction was carried out in a high-temperature, high-pressure reactor at 270 °C for 4 h. After the reaction, the mixture was cooled to room temperature, and the liquid-solid mixture was filtered and separated. The isopropanol in the liquid phase was removed by rotary evaporation. Then, 1 mol / L hydrochloric acid was added to adjust the pH to 1, and the mixture was extracted three times with ethyl acetate. The upper liquid was dried with anhydrous MgSO4, and then the ethyl acetate was removed by rotary evaporation to obtain 0.655 g of liquid product, i.e., the liquid phase product yield reached 62.5%, and the phenol monomer selectivity was 44.0%.
[0117] The liquid phase yield and monomer phenol selectivity of the lignin depolymerization reaction in the above examples and comparative examples are statistically shown in Table 1. Table 2 shows the BET characterization results of the catalysts obtained in Example 1 and Comparative Example 5.
[0118] Table 1. Statistical Table of Evaluation Results of Lignin Depolymerization Reaction
[0119] Project Name Liquid phase yield / wt% Monomer phenol selectivity / % Example 1 76.9 48.7 Example 2 76.4 51.2 Example 3 75.9 53.4 Example 4 78.1 50.9 Example 5 71.3 50.1 Example 6 78.4 53.4 Example 7 76.0 49.4 Comparative Example 1 56.0 43.5 Comparative Example 2 58.7 46.3 Comparative Example 3 60.3 40.8 Comparative Example 4 66.3 46.6 Comparative Example 5 62.5 44.0
[0120] Table 2. Characterization analysis results of BET catalysts in Example 1 and Comparative Example 5.
[0121] Project Name <![CDATA[Specific surface area m 2 / g]]> Example 1 86 Comparative Example 5 71
[0122] As can be seen from the depolymerization reaction results of Comparative Examples 1-3 in Table 1, the catalysts prepared by the one-step reduction method have lower product yield and monomer phenol selectivity than the catalysts prepared in this invention. This is mainly because the one-step reduction method easily leads to agglomeration between the catalytic active element and the co-catalytic active element, resulting in the inability of the catalytic sites on the prepared catalyst surface to fully exert their catalytic effect. This invention employs a two-step reduction method, which reduces some Ni elements in the solid alkali oxide crystal phase to create defects, thereby achieving efficient loading of Ru elements at the defect sites. Furthermore, this invention avoids the agglomeration of Ru elements during the loading process by preparing a Ru(CH3COO)3 solution. The Ru elements are highly dispersed on the surface of the catalytic active component, which can fully exert their co-catalytic effect, thereby further improving the catalytic effect of the catalyst. The reaction results of Comparative Example 4 show that reducing the Ru element loading reduces the co-catalytic effect, leading to a decrease in the depolymerization reaction activity of the catalyst. The reaction results of Comparative Example 5 show that reducing the amount of steric hindrance agent is not conducive to the growth of the layered structure of LDH precursor. Combined with the specific surface area data of Example 1 and Comparative Example 5 in Table 2, it can be seen that reducing the amount of steric hindrance agent will reduce the specific surface area of the precursor, which will limit the loading of subsequent catalytic active elements and thus have an adverse effect on the catalyst activity.
[0123] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a Ru-Ni / NiO-MMO catalyst, wherein, The preparation method includes the following steps: 1) Ni(NO3)2·6H2O, Mg(NO3)2·6H2O, metal nitrate A, and steric hindrance B are dissolved in a solvent, wherein the metal nitrate A is selected from at least one of Fe(NO3)3·9H2O, Al(NO3)3·9H2O, and Co(NO3)3·6H2O; the pH of the solution is adjusted to 8-12 and then a hydrothermal crystallization reaction is carried out; after the reaction is completed, the temperature is lowered to room temperature, the solid is separated, washed, dried, and ground into powder to obtain the Ni-based LDHs precursor; 2) The Ni-based LDHs precursor was calcined in air and then reduced in a H2 / N2 mixture to obtain NiMg. 1- 4A 1-1.5 O y , where y: 3.0~6.0; 3) The NiMg 1-4 A 1-1.5 O y The Ru-Ni / NiO-MMO precursor was obtained by immersing the precursor in an aqueous solution of Ru(CH3COO)3 for a predetermined time and then drying it. 4) The Ru-Ni / NiO-MMO precursor was calcined in an N2 atmosphere and then reduced in an H2 / N2 mixture to obtain Ru-Ni / NiO-MMO.
2. The preparation method according to claim 1, wherein, The molar ratio of Ni(NO3)2·6H2O, Mg(NO3)2·6H2O and metal nitrate A is 1:(1~4):(1~1.5).
3. The preparation method according to claim 1, wherein, The steric hindrance agent B is selected from at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, F127, and P123.
4. The preparation method according to claim 1, wherein, The amount of steric hindrance agent B added is 1 to 2 times the mass of metal nitrate A.
5. The preparation method according to claim 1, wherein, The solvent is an ethanol-water mixture, wherein the volume percentage of ethanol in the ethanol-water mixture is (5-30) vol.%.
6. The preparation method according to claim 1, wherein, The hydrothermal crystallization reaction is carried out at a temperature of 150–200°C for 10–24 hours.
7. The preparation method according to claim 1, wherein, The calcination temperature in the air atmosphere is 600–1000℃, and the time is 6–12 hours.
8. The preparation method according to claim 1, wherein, In step 2), the reduction temperature is 400–800°C and the reduction time is 4–10 h.
9. The preparation method according to claim 1, wherein, The Ru-Ni / NiO-MMO precursor was calcined in an N2 atmosphere at a temperature of 300–600 °C for 2–8 h.
10. The preparation method according to claim 1, wherein, In step 4), the reduction temperature is 400–800°C and the reduction time is 2–10 h.
11. A Ru-Ni / NiO-MMO catalyst, obtained by the preparation method according to any one of claims 1-9.
12. A method for using the Ru-Ni / NiO-MMO catalyst of claim 11 in the catalytic hydrogenolysis of lignin, wherein, The method includes the following steps: Lignin and the Ru-Ni / NiO-MMO catalyst were added to a hydrogen-donating solvent and depolymerized at 200–350 °C. After the reaction was completed, the mixture was cooled to room temperature and filtered. The hydrogen-donating solvent was removed from the liquid phase. Then, hydrochloric acid solution was added for acidification, followed by extraction with ethyl acetate. The upper liquid was dried and the ethyl acetate was removed to obtain the liquid product.
13. The application method according to claim 12, wherein, The mass ratio of lignin to Ru-Ni / NiO-MMO catalyst is 1:(0.5-2).
14. The application method according to claim 12, wherein, The hydrogen-donating solvent is selected from at least one of ethanol, isopropanol, n-butanol, sec-butanol, and tert-butanol.
15. The application method according to claim 12, wherein, The depolymerization reaction takes 2 to 12 hours.
Citation Information
Patent Citations
Method for preparing cyclohexanol and derivatives thereof by selective hydrogenolysis of lignin
CN112341312A
RuNi-loaded hydrotalcite oxide as well as preparation method and application thereof
CN113231075A
In-situ hydrogenolysis aryl ether bond catalyst as well as preparation method and application thereof
CN114029070A